TO THE PROBLEM OF PROFESSIONAL FORMATION COMPETENCIES OF FUTURE TEACHERS-PHILOLOGISTS1B BY MEANS OF DIALOGICAL SITUATIONS (Pedagogy of Higher and Secondary Education, 2022)
This article considers the problem of the formation of the professional competence of a teacher in the context of making the training more dialoguing.